STRATEGI PENGELOLAAN DANA BANTUAN SOSIAL(SOCIAL ASSISTANCE FUNDS MANAGEMENT STRATEGY) - Irham Iskandar (Inovasi, 2017)
The main objective of this study was to determine the strategy of the fund management bansos through SWOT approach. The method used is the development of research, the research is intended to develop research findings or theories before, both for pure science and applied science, and so on. The data used are primary data and secondary data. The primary data obtained through interviews with a sample using a questionnaire and in-depth interviews with informants, while secondary data obtained through library consisting of journals, scientific reports, official government reports, and other materials relevant. Data analysis using descriptive qualitative method, namely in the form of data - the data obtained statistically illustrates the tabulation in the form of tables, graphs, and maps. Further testing will be done kuisoener data using descriptive statistics equipment. The results showed that internal factors relative business groups have more weakness versus strength. But of external factors as business development opportunities are relatively better than a challenge. This indicates that the policy strategy needs to be done in the coaching business group is utilizing the group members actively participate in group decision-making process from planning, implementation, control and maintenance activities as well as increasing the role of mentoring institution that helps smooth the member / group effort. Keywords: social grants, SWOT approach, internal and external factors